An onfarm rice variety trial in toposequences of inland valley swamps - Palada, M.C.; Walker, P.; Masajo, T.M.; Jalloh, M. (1991)
The use of a statistical tool such as the analysis of variance is effective in estimating experimental errors and detecting the Importance of factors such as toposequence, paddy status, site and variety as determinants of rice yields in IVS. Based on the analysis, the important factors affecting rice yield in both locations (Bida and Makeni) are toposequence and variety. In Bida, the effects of site and paddy status were not important. The slight differences in yield due to these factors can be attributed to somewhat improved farmers' paddy with minimum bunding and water control. Using site and paddy status as covariates and excluding one variety which performed poorly in one site, Significant effects of toposequence and variety were enhanced. In Makeni, the linear effect of toposequence on yield was highly signiftcant. The interaction between toposequence and variety was more apparent in Makeni than in Bida. Average yield in the valley bottom was about two to three times higher than in the valley fringe and in1ddle slope. In Bida three improved varieties consistently and significantly yielded higher than the common variety, FARO 15, across toposequence, whereas in Makeru, two improved varieties consistently out yielded the local check across toposequence.